2014
DOI: 10.1097/tp.0000000000000314
|View full text |Cite
|
Sign up to set email alerts
|

Results of Life-Supporting Galactosyltransferase Knockout Kidneys in Cynomolgus Monkeys Using Two Different Sources of Galactosyltransferase Knockout Swine

Abstract: Background Various durations of survival have been observed in the xenotransplantation of life-supporting alpha-1,3-galactosyltransferase knockout (GalT-KO) porcine kidneys into nonhuman primates (NHPs). While others have demonstrated loss of GalT-KO transplanted kidneys within two weeks, we have reported an average survival of 51 days with the co-transplantation of the kidney and vascularized thymus and an average of 29 days with the kidney alone. In order to determine the factors responsible for this differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
73
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(80 citation statements)
references
References 24 publications
7
73
0
Order By: Relevance
“…Yamada et al have demonstrated the correlation of pCMV positivity of donors and markedly shortened survival of pig-to-primate renal transplants (48-days to 14-days) in their model (7). In a parallel study, transplantation of pCMV positive vs. negative kidneys into cynomolgous monkeys, shortened survival from an average of 28.7-days to 9.2-day (23). The accelerated graft loss occurred as a result of early rejection, accompanied by disseminated vascular coagulation and thrombocytopenia, similar to what was observed in our only recipient of a pCMV positive xenoliver (Baboon #3).…”
Section: Discussionmentioning
confidence: 99%
“…Yamada et al have demonstrated the correlation of pCMV positivity of donors and markedly shortened survival of pig-to-primate renal transplants (48-days to 14-days) in their model (7). In a parallel study, transplantation of pCMV positive vs. negative kidneys into cynomolgous monkeys, shortened survival from an average of 28.7-days to 9.2-day (23). The accelerated graft loss occurred as a result of early rejection, accompanied by disseminated vascular coagulation and thrombocytopenia, similar to what was observed in our only recipient of a pCMV positive xenoliver (Baboon #3).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, there was a three year period after 2008 in which renal xenograft survival was decreased markedly (<3 weeks), even with thymic co-transplantation (58). We investigated potential causes of this early loss and found a strong association of porcine cytomegalovirus (pCMV) infection in GalT-KO porcine kidneys with decreased graft survival (58, 59). We subsequently tested for pCMV in donor splenocytes and/or in the explanted kidney grafts in 53 cases.…”
Section: Donor Factorsmentioning
confidence: 99%
“…Second, microbiological characterization of the donor pigs has, in the past, not been sufficiently thorough, and as a result, pig to non-human primate transplantations have been performed that resulted in the transmission of pathogenic microorganisms and the premature death of the recipients. For example, the transmission of PCMV to cynomolgus monkeys and baboons, significantly reducing survival time, has been reported [62,63]. Additional financial support and scientific investigations have to be devoted to studies of viral safety, the results of which should automatically contribute to increasing the survival times of xenotransplants and their recipients.…”
Section: Discussionmentioning
confidence: 99%
“…HCMV infections are in many cases fatal for immunosuppressed allotransplant recipients [71]. Although PCMV is more closely related to HHV-6 and HHV-7 than to HCMV, designated now as HHV-5 [72], it has been shown that transmission of PCMV in pig to non-human primate kidney transplantation drastically reduced the survival time of the recipients [62,63], suggesting that PCMV may have a similar effect in humans. PLHV-1, -2, and -3 were found in large numbers on farm pigs (in 78%, 41%, and 59% of the lung tissue samples, and in 59%, 26% and 62% of the spleen samples, respectively [73]).…”
Section: Microbiological Safetymentioning
confidence: 99%
See 1 more Smart Citation